An Evaluation for an ESP Course for Mechanical Engineering Students - Jonathan Calderón Bailey (Revista de Lenguas Modernas, 2019)
When designing a course, it is important to take into account the accomplishment of the goals set beforehand in order to evaluate the success of the process. This work presents the design, implementation, and evaluation of outcomes of an English for Specific Purposes course for Mechanical Engineering students. For this, the principles of Task-Based Language Teaching and English for Specific Purposes were followed in order to create a course that addressed the language needs of a group of students from the Mechanical Engineering major at the University of Costa Rica. A mixed methods approach was followed to analyze the data and present the results. The data was analyzed using the students’ performance in certain tasks and their perception of how well they performed them. Based on the three goals established, the results showed that most participants achieved them to great or some extent.